OpenCV 3.x with Python by example : make the most of OpenCV and Python to build applications for object recognition and augmented reality /: make the most of OpenCV and Python to build applications for object recognition and augmented reality. (2018) - Garrido, Gabriel; Joshi, Prateek
No abstract available